Refractive error, ocular and general parameters and ophthalmic diseases: the Beijing Eye Study - Xu, Liang; You, Qisheng; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2010)
To assess relationships between refractive error and ocular and general parameters.